A new insight into the treatment of diabetes by means of pan PPAR agonists. (17th January 2022) - Chandra, Avik; Kaur, Paranjeet; Sahu, Sanjeev Kumar; Mittal, Amit
Abstract: PPARs stand for 'peroxisome proliferator‐activated receptors' and are ligand‐activated transcription factors of nuclear hormone receptor superfamily. A list of the most commonly used single receptor PPAR agonists, that is α (alpha) PPAR agonists, β/δ(beta/delta) PPAR agonists, γ(gamma) PPAR agonists, along with pan PPAR agents, that are being researched on, are marketed, are in clinical trials or are being studied for further derivative findings, has been listed. Type 2 diabetes constitutes about 90% of total diabetes cases. Pan PPAR ligands could very well pave the foundation for a new class of agents, that can act on all 3 PPAR receptors, and produce better effects in general, than the individual receptor‐acting ligands or dual combination ligands (α/ γ). In this review paper, we have detailed various pan PPAR agonists that can be used to treat type 2 diabetes, which can generate potential derivatives as well. Abstract : This review is focused on several pan PPAR agonists, which could lead to the development of potential derivatives for the management of type 2 Diabetes.